The Effect of Macroeconomic Indicators on Profitability and Firm Value - Made Reina Candradewi; Henny Rahyuda (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The objective of this study encompasses an examination of the influence of inflation, gross domestic product, and profitability on the valuation of companies within the Indonesian stock market, with specific emphasis on corporations listed in the LQ45 index on the Indonesia Stock Exchange (IDX). The LQ45 index as it offers a focused and comprehensive view of the Indonesian stock market, allowing them to draw meaningful conclusions about the impact of inflation, GDP, profitability, and other factors on the valuation and performance of these selected companies. The primary aim of this research is to provide valuable insights to corporations regarding the significance of maintaining profitability and firm value while taking into consideration macroeconomic indicators. The research methodology employed in this investigation is of a quantitative nature. The study encompasses the entirety of companies listed within the LQ45 Index on the IDX as the designated population. The technique employed for sample selection is purposive sampling. The selected sample comprises companies that have consistently maintained their listing in the LQ45 Index on the IDX from 2016 to 2022, totaling 31 companies. The outcomes of the goodness-of-fit examination and the robustness assessment of the model utilized within this study unequivocally affirm the model's exceptional effectiveness in aligning with the available dataset. The analysis of the results of the regression analysis and the mediation assessments leads to the definitive conclusion that the Gross Domestic Product variable exerts a remarkably positive and statistically significant influence on Firm Value. Likewise, the Profitability variable significantly and positively impacts firm value. However, it is imperative to acknowledge that profitability does not function as a mediating factor in the relationship between Inflation and Gross Domestic Product in the context of firm value.